Metafora „wiedza to widzenie” w różnych systemach semiotycznych i dyskursach - Lipszyc, Weronika (Załącznik Kulturoznawczy, 2021)
The article refers to the presence of the metaphor ‘understanding is seeing’ in various semiotic systems and discourses, pointing to the dominance of cognitive function of metaphor and the unification of sensory experience and mental cognition within it. Outlined is the context in which the emergence of the identification of knowledge with sight takes place and the establishment of this epistemological metaphor, important for Western culture (an oculocentric discourse). The presence of metaphor in visual arts, polysemiotic arts, and music is analyzed, with the indication of the multisensory nature of perceptual experiences (the perspective of rhetorical research on heterosemiotic cultural phenomena is adopted here). In the further part of the text, the role of metaphor in scientific and artistic discourse and media communication is examined, as well as the perspective of the development of the ‘visual field’ in the face of wear out of metaphor, the co-presence in culture of oculocentric and oculophobic tendencies, and the digital remediatization of cultural texts.